Sequence analysis of serum paraoxonase 1 of bathyergidae family specific rats - SUBHAMAY PANDA,; SUBHAJIT HAZRA, (International Journal of Pharma and Bio Sciences, 2016)
Initially characterized as an organophosphate hydrolase, paraoxonase (PON) was seen to catalyses the hydrolysis of paraoxon organophosphate insecticides and sarin nerve gases as well as other similar compounds. The paraoxonase gene cluster contains three adjacent gene members, PON1, PON2, and PON3. Emerging from the same lactonase precursor (fungus), all of the PON genes share profound level of sequence identity and a very similar β propeller protein structure. Formerly a study on the structural characterization of arylesterase (paraoxonase) of Ancylostoma duodenale was done to understand their structural improvements. The objective of this study was to determination of protein sequence level characteristics of PON1 of bathyergidae family specific rats (naked mole rat (Heterocephalus glaber) and Damaraland mole rat (Fukomys damarensis) with the help of different bioinformatical tools. The present study clearly demonstrates that protein evolution occurred within the bathyergidae family specific rats i.e., in naked mole rat and Damaraland mole-rat.